Three-dimensional finite element analysis of silk protein rod implantation after core decompression for osteonecrosis of the femoral head - Huang, Liangta (BMC Musculoskelet Disord, 2019)
BACKGROUND: Several methods are available for the treatment of early-stage osteonecrosis of the femoral head. Core decompression with implantation is a widely-used treatment. However, no single implant is recognized as the most effective way to prevent disease progression. Silk has high strength and resiliency. This study explored the possibility of a strong and resilient silk protein biomaterial as a new alternative implant. METHODS: We investigated the biomechanical properties of the silk protein material by regular compression, torsion, and three-point bending tests. We established three-dimensional finite element models of different degrees of femoral head osteonecrosis following simple core decompression, fibula implantation, porous tantalum rod implantation, and silk protein rod implantation. Finally, we compared the differences in displacement and surface stress under load at the femoral head weight-bearing areas between these models. RESULTS: The elastic modulus and shear modulus of the silk protein material was 0.49GPa and 0.66GPa, respectively. Three-dimensional finite element analyses demonstrated less displacement and surface stress at the femoral head weight-bearing areas following silk protein rod implantation compared to simple core decompression (p < 0.05), regardless of the extent of osteonecrosis. No differences were noted in the surface deformation or surface stress of the femoral head weight-bearing areas following silk protein rod, fibula or tantalum rod implantation (p > 0.05). CONCLUSIONS: When compared with simple core decompression, silk protein rod implantation demonstrated less displacement and surface stress at the femoral head weight-bearing area, but more than fibula or tantalum rod implantation. Similar effects on the surface stress of the femoral head between the silk rod, fibula and tantalum rod implantations, combined with additional modifiable properties support the use of silk protein as a suitable biomaterial in osteonecrosis surgery.